2011
DOI: 10.1007/s00520-011-1337-z
|View full text |Cite
|
Sign up to set email alerts
|

Chore or priority? Barriers and facilitators affecting dilator use after pelvic radiotherapy for gynaecological cancer

Abstract: This is the first qualitative study to specifically investigate the patient experience of dilator use. The barriers and facilitators identified in this study and the proposed theory-based model provide new insights to inform future research and clinical management of dilator use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 16 publications
4
43
0
1
Order By: Relevance
“…We did not explore positive influences, or “facilitators,” to adherence. One qualitative study of 15 participants [26] originally identified barriers and facilitators of VD use. The lack of standardized VS measures and methods of addressing VS makes it difficult to correlate results from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…We did not explore positive influences, or “facilitators,” to adherence. One qualitative study of 15 participants [26] originally identified barriers and facilitators of VD use. The lack of standardized VS measures and methods of addressing VS makes it difficult to correlate results from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Issues of consistency of information are often highlighted by authors describing rehabilitation to prevent vaginal stenosis after pelvic radiotherapy [12–14]. Miles and Johnson [15] in their 2014 update of a Cochrane Review into vaginal dilator therapy concluded that there is no reliable evidence supporting dilator therapy during radiotherapy treatment, and while several observational studies of dilator therapy after radiotherapy treatment suggest an association between frequent dilator therapy and a reduction in self‐reported stenosis, they acknowledge that there is no proof that a decrease in stenosis is an effect of the dilator therapy.…”
Section: Information Needsmentioning
confidence: 99%
“…Miles and Johnson [15] in their 2014 update of a Cochrane Review into vaginal dilator therapy concluded that there is no reliable evidence supporting dilator therapy during radiotherapy treatment, and while several observational studies of dilator therapy after radiotherapy treatment suggest an association between frequent dilator therapy and a reduction in self‐reported stenosis, they acknowledge that there is no proof that a decrease in stenosis is an effect of the dilator therapy. With no clear evidence as to the benefit of a rehabilitation therapy, there is inevitably a range of recommendations and advice given to patients [14].…”
Section: Information Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurse will address any ongoing issues from the first session and new concerns and provide coaching in relevant self-care. Barriers to self-care and stress-reduction strategies will be elicited and the importance of adherence reinforced [42]. …”
Section: Methodsmentioning
confidence: 99%